Patofisiologi, Klasifikasi, dan Tatalaksana pada Grave’s Ophthalmopathy - Ritsia Anindita Wastitiamurti (Jurnal Kedokteran Meditek, 2018)
Grave’s ophthalmopathy (GO) happens in 40% of patients who suffer from Grave’s hyperthyroidism. The underlying cause of GO is an immunology response that effects not only the thyroid but also the eyesl. Without proper management, GO may cause loss of vision. The risk of GO in Grave’s disease increases with the presence of several risk factors such as older age and smoking history. Anatomical and histological changes to the soft tissues of the orbit cause the eye to protrude (exophtalmus) which is clinically a significant sign to this disease. Proper examination and follow ups of these patients are critical to decide the management to be taken. The management would depend on the phase (active and inactive) and the severity of this disease which was chategorized from mild to sight threatening.Keywords : pathophysiology, classification, management, grave’s ophthalmopathy